Documentary Film as A Tool For Environmental Advocacy In Indonesia:A Literature Review - Endah Wahyu Sulistianti, Endah Wahyu Sulistianti (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2025)
Documentary films have increasingly become a medium for environmental advocacy worldwide. In Indonesia, where environmental issues such as deforestation, biodiversity loss, and human-wildlife conflict are pressing concerns, documentary films serve as powerful tools for raising awareness and influencing public discourse. However, scholarly research on how Indonesian documentaries contribute to environmental advocacy remains limited. This literature review examines existing studies on Indonesian environmental documentaries, identifying key themes, challenges, and gaps in research. It explores how these films shape public perception, engage policymakers, and impact grassroots activism. The study highlights the role of digital streaming platforms in expanding the reach of environmental documentaries, particularly in engaging younger audiences. By analyzing previous research and identifying areas for further investigation, this review provides insights into the potential of documentary films as catalysts for environmental change in Indonesia.